2021
DOI: 10.1007/978-3-030-82269-9_15
|View full text |Cite
|
Sign up to set email alerts
|

Human Gender Detection from Facial Images Using Convolution Neural Network

Abstract: Human gender detection which is a part of facial recognition has received extensive attention because of it's different kind of application. Previous research works on gender detection have been accomplished based on different static body feature for example face, eyebrow, hand-shape, body-shape, finger nail etc. In this research work, we have presented human gender classification using Convolution Neural Network (CNN) from human face images as CNN has been recognised as best algorithm in the field of image cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…Result of CNN. However, utilizing hybrid feature vectors into classification attained lower accuracy (95%) than applying the geodesic technique to extract features, see Table 2 [20] 85.5% Singh et al [21] 95.5% Bekhouche et al [4] 88.8 Balci and Atalay [22] 92% Abdelkader and Griffin [23] 85% Makenen et al [24] 84% Yang et al [25] 93% Agbo-Ajala and Viriri [27] 89.7% Khalifa et al [28] 98.88% Haider et al [29] 98% Duan et al [30] 88.2% Tilki et al [31] 92.4% Sumi et al [32] 97.44% Dhomne et al [ 96.5% Hosoi et al [10] 94.33% Roomi et al [11] 81% Biag et al [12] 84.91% Khan et al [13] 93.2, 92, 99.2, 100 Masood et al [14] 98.6% Vo and Le [15] 91% Greco et al [16] 94.1% Heng et al [17] 95.2% Proposed method 100%…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Result of CNN. However, utilizing hybrid feature vectors into classification attained lower accuracy (95%) than applying the geodesic technique to extract features, see Table 2 [20] 85.5% Singh et al [21] 95.5% Bekhouche et al [4] 88.8 Balci and Atalay [22] 92% Abdelkader and Griffin [23] 85% Makenen et al [24] 84% Yang et al [25] 93% Agbo-Ajala and Viriri [27] 89.7% Khalifa et al [28] 98.88% Haider et al [29] 98% Duan et al [30] 88.2% Tilki et al [31] 92.4% Sumi et al [32] 97.44% Dhomne et al [ 96.5% Hosoi et al [10] 94.33% Roomi et al [11] 81% Biag et al [12] 84.91% Khan et al [13] 93.2, 92, 99.2, 100 Masood et al [14] 98.6% Vo and Le [15] 91% Greco et al [16] 94.1% Heng et al [17] 95.2% Proposed method 100%…”
Section: Discussionmentioning
confidence: 99%
“…It achieved better accuracy when using the proposed CNN (92.4%) compared with AlexNet (90.5%). Sumi et al[32] also suggested a new CNN model for feature extraction from face images and gender classification. They passed face images through convolution layers, RELU and max-pooling layer to extract features.…”
mentioning
confidence: 99%
“…For Gender Recognition, various techniques, such as facial photographs [6], hand images, and pose/body images [7], can be used to identify gender. By extracting two different sorts of characteristics, gender recognition is accomplished [8,10].…”
Section: Literature Surveymentioning
confidence: 99%
“…Comparing the proposed method with some of the previous techniques for gender classification is listed in Table 12 for face images and Table 13 for eyes images. (Sumi et al, 2021) Kaggle dataset, Nottingham scan 97.44,90 Deep CNN (Yildiz et al, 2021) Adience, VGGFace2 85.52,93.71 Pareto frontier CNN (Islam et al, 2020) WIKI-cleaned 90 Pre-trained CNN (Zhou et al, 2019) Adience 93.22 VGGNet arch (Dhomne et al, 2018) Celebrity faces 95 Hyper face (Ranjan et al, 2017) CelebA, LFWA 98,94 Face tracer (Kumar et al, 2008) CelebA, LFWA 84,91 Deep CNN (Kamaru, 2020) CelebA, LFWA 96,95 Deep CNN (Benkaddour et al, 2021) WIKI, IMDB 93.56,94.49 CNN + ELM (Extreme Learning Machine) (Micheala and Shankar, 2021) Adience 90.2 LMTCNN (Lightweight Multi-task CNN) (Lee et al, 2018) Adience 85 Wide CNN + Gabor Filter (Hosseini et al, 2018) Adience 88.9 2DPCA on real Gabor space + SVM (Rai and Khanna, 2015) LFW…”
Section: Train the Cnn Model On Eyes From Different Datasetsmentioning
confidence: 99%